中国软力量和新加坡华人的文化认同 = China’s soft power and the cultural identity of Singaporean Chinese - 魏瑜嶙 Hoi, Elyn (2010)
“软力量”（Soft Power）作为一个新的名词在1990年由美国学者Joseph Nye提出，而软力量的概念在近几年也越来越受到中国政府的重视。不过纵观历史，软力量虽无其名却早已有其实。中国软力量早在新加坡开埠之初便以随着中国移民来到本地。从最早中国移民所带来的华族文化，到后来无论是清政府、民国政府或新中国政府通过各个管道输入本地的中国软力量，皆对新加坡华人的文化认同造成一定的影响。新加坡独立之前，本地的华人社群对中国抱有强烈的认同感，反映在他们在华文教育和华族文化方面对中国输入本地的软力量的回应。新加坡独立之后，中国软力量通过新加坡政府接收之后转换成一些政策再传递给本地的华人社群。而新加坡政府与本地华人也在各方面对中国输入我国的软力量作出回应。因此，笔者将通过对历史事件的观察以及对目前新加坡政策的一些发展动向，透过来讨论中国软力量如何对新加坡华人的文化认同造成影响。 “Soft power” is a new term coined by Joseph Nye in 1990, and it is fast gaining popularity among the Chinese leaders in recent years. Although soft power is a fairly new term, we do see the operation of the characteristics of soft power throughout Chinese history. As early as in 1819, China’s soft power reached Singapore with the arrival of Chinese migrants. From the very beginning, Chinese migrants brought with them their culture when they migrated to Singapore and as time progressed, the Qing authorities, the ROC and the CCP governments, all tried to export China’s soft power to Singapore via various means and channels. Undeniably, this soft power did have an impact on the cultural identity of Singaporean Chinese from time to time. Before Singapore’s independence, the Chinese here in Singapore identified strongly with the Chinese government which was then reflected in how they responded to China’s soft power in aspects of Chinese education and culture.